Adenine Nucleotide Metabolism of Human Platelets - Murakami, M; Odake, K (Thrombosis and Haemostasis, 1971)
After platelet-rich plasma was incubated with radioactive adenine, radioactive adenine nucleotides in platelets were separated by two-dimensional thin-layer chromatography.Radioactive adenine was selectively incorporated into adenine nucleotides. Gradual decomposition of labelled nucleotides was observed after longer period of incubation. Radioactive ATP, ADP, AMP, IMP, and hypoxanthine were separated from PCA extract of platelets. On the other hand, radioactive adenine and hypoxanthine were separated from platelet-poor plasma.After thrombin treatment, radioactive ATP in platelets broke down rapidly, while radioactive ADP decreased more slowly. Radioactive AMP increased at first in the cellular and supernatant fractions, and then decreased gradually. The accumulation of radioactive hypoxanthine was observed in the supernatant fraction. Released radioactive ATP and ADP were 23% and 22% of the initial radioactive ATP and ADP in platelets, respectively.